2013
DOI: 10.1364/oe.21.013896
|View full text |Cite
|
Sign up to set email alerts
|

Giant optical nonlinearity of a single plasmonic nanostructure

Abstract: We realize giant optical nonlinearity of a single plasmonic nanostructure which we call a split hole resonator (SHR). The SHR is the marriage of two basic elements of nanoplasmonics, a nanohole and a nanorod. A peak field intensity in the SHR occurs at the single tip of the nanorod inside the nanohole. The peak field is much stronger than those of the nanorod and nanohole, because the SHR field involves contributions from the following two field-enhancement mechanisms: (1) the excitation of surface plasmon res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 33 publications
0
63
1
Order By: Relevance
“…Apertures efficiently remove heat because of the surrounding metal film having a high thermal conductivity. For the same local intensity, the heating can be four orders of magnitude smaller than similar plasmonic nanoparticles [154]. (These particles are similar in the sense that they create the same local field intensities on resonance.)…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…Apertures efficiently remove heat because of the surrounding metal film having a high thermal conductivity. For the same local intensity, the heating can be four orders of magnitude smaller than similar plasmonic nanoparticles [154]. (These particles are similar in the sense that they create the same local field intensities on resonance.)…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…Our measurements and calculations showed that the THG efficiency of the SHR nanostructure strongly depends on its geometry (the nanostructure diameter, the nanorod length, the film thickness), the material of the film, and the refractive index of the medium surrounding the SHR [5]. This behavior is explained by the wellknown strong dependence of the excitation efficiency of localized plasmon oscillations on the geometry of the nanostructure and its local environment, which determines the distribution and amplitude of the electromagnetic field near the nanostructure.…”
Section: Nonlinear Optical Properties Of a Single Shr Nanostructurementioning
confidence: 85%
“…The absolute value of the transformation efficiency of the excitation radiation into the third harmonic per unit area (the intensity ratio of the third-harmonic radiation and the radiation at the fundamental frequency) is about 10 -5 , which is a record high value for experiments on the THG from single nanostructures [5]. Up to now the maximum conversion efficiency of THG was as high as 3 × 10 -7 and was realized on nanostructures in a shape of a split-ring resonator [6].…”
Section: Nonlinear Optical Properties Of a Single Shr Nanostructurementioning
confidence: 99%
“…In practice, the laser beam intensity at the fundamental frequency is limited by a value of ~10 10 W cm -2 . The record values of harmonic generation efficiency are on the order of ~10 -6 [29,34,36], which, at first glance, seems to be very low. However, one must also take into account the extremely small nanostructure volume with which laser radiation interacts.…”
Section: Introductionmentioning
confidence: 97%
“…It was demonstrated in [34] that, controlling the nanostructure geometry, one can control the character of its nonlinear optical interaction with laser radiation. For example, the formation of a nanostructure with roughness having a characteristic size of about 10 nm may leads to dominance of the individual-electron dynamics; as a consequence, nonlin-Third harmonic generation in the short-wavelength UV range by a single plasmonic nanostructure ear optical interaction manifests itself as multiphoton luminescence.…”
Section: Introductionmentioning
confidence: 99%